2009
DOI: 10.1016/j.gep.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of prostaglandin endoperoxide synthase expression in the ovine fetal central nervous system and pituitary

Abstract: In this study, we tested the hypothesis that prostaglandin endoperoxide synthase -1 and -2 (PGHS-1 and PGHS-2) are expressed throughout the latter half of gestation in ovine fetal brain and pituitary. Hypothalamus, pituitary, hippocampus, brainstem, cortex and cerebellum were collected from fetal sheep at 80, 100, 120, 130, 145 days of gestational age (DGA), 1 and 7 days postpartum lambs, and from adult ewes (n=4-5 per group). mRNA and protein were isolated from each region, and expression of Prostaglandin Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…What is unclear is where this interaction occurs. PGHS-2 abundance is highest in the cerebral cortex and hippocampus, with lower expression in the hypothalamus and brain stem (8). This pattern of expression in the fetal sheep is similar to that in the adult rat (8,13).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…What is unclear is where this interaction occurs. PGHS-2 abundance is highest in the cerebral cortex and hippocampus, with lower expression in the hypothalamus and brain stem (8). This pattern of expression in the fetal sheep is similar to that in the adult rat (8,13).…”
Section: Discussionmentioning
confidence: 54%
“…PGHS-2 abundance is highest in the cerebral cortex and hippocampus, with lower expression in the hypothalamus and brain stem (8). This pattern of expression in the fetal sheep is similar to that in the adult rat (8,13). The infusion of nimesulide reduces prostaglandin generation throughout the brain (7), and general levels of expression of PGHS-2 do not provide useful clues as to which regions are important with regard to NMDA-PGHS-2 interactions in control of the fetal HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary was not used in the present study. Gene expression studies for estrogen receptor and prostaglandin synthase isoforms and for components of the fetal hypothalamus-pituitary-adrenal axis have been previously performed on these tissues and previously reported 4, 17, 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the negative effect of ketamine and denervation was apparent in hippocampus. We have consistently found that the level of expression of PGHS in late gestation fetal sheep is highest in hippocampus and cerebral cortex 33 ; perhaps it should not be surprising that a manipulation that reduces expression would be best observed in structures with the highest expression levels.…”
Section: Discussionmentioning
confidence: 70%